Hak Mogok Kerja dalam Perspektif Yuridis dan Sosiologis - Willy Farianto (Fakultas Hukum Universitas Islam Indonesia, 2014)
Issues raised in this paper are: First, how do we know whether the strike conducted by the employers is a legal one? Second, how do we protect employers from some invalid strike actions? This research is a normative juridical (legal normative research). The approach used in this study is legislative approach (statute approach) and the conceptual approach. The study concluded, first, that employers’ strikes will belong to legal ones if: a) a deliberation about the specifics of disputes between the unions and employers has been truly held; b) the request of negotiation has been truly rejected by the owners; c) they has been failed in two times within a period of two (2) weeks to invite other parties to negotiate. Second, the employer could do either the refusal to the implementation of a strike in the framework of the three stages; before, during and after the strike; or did lock out done by the owners.